Learning SAS by example : a programmer's guide - Cody, Ronald P. (SAS Press series., 2007)
If you like learning by example, then this straightforward book makes it easy to learn SAS programming. In an instructive and conversational tone, author Ron Cody clearly explains each programming technique and then illustrates it with one or more real-life examples, followed by a detailed description of how the program works. The text is divided into four major sections: Getting Started; DATA Step Processing; Presenting and Summarizing Your Data; and Advanced Topics. Subjects addressed include: Reading data from external sources Learning details of DATA step programming Subsetting and combining SAS data sets Understanding SAS functions and working with arrays Creating reports with PROC REPORT and PROC TABULATE Learning to use the SAS Output Delivery System Getting started with the SAS macro language Introducing PROC SQL You can test your knowledge and hone your skills by solving the problems at the end of each chapter. (Solutions to odd-numbered problems are located at the back of this book. Solutions to all problems are available to instructors by visiting the book's companion Web site for details.) This book is intended for beginners and intermediate users. Readers should know how to enter and submit a SAS program from their operating system. Includes a CD-ROM with the example code, data sets, and solutions to odd-numbered problems.